Variasi Lama Kejutan Panas pada Suhu yang Sama terhadap Tingkat Penetasan Telur (HR) Ikan Lele Dumbo (Clarias gariepinus) - Anny Rimalia (Al-Hayat: Journal of Biology and Applied Biology, 2020)
Species, temperature shock duration, fertilization temperature from different climates can cause different hatching results, so it is necessary to do research on the treatment of variations in heat shock at the same temperature, to obtain information about the hatching rate (HR) of African catfish (Clarias gariepinus). The method used is completely randomized design (3x3). The results of the egg hatching rate (HR), with variations in the heat shock at the same temperature (35⁰C), showed the highest rate of hatching dumbo catfish eggs at heat shock one minute 233.00%, then heat shock two minutes 212.00%, and heat shock three minutes 200.00% respectively.